Penilaian model empirik keupayaan galas tanah baki sedimen daripada kaedah gelombang permukaan - Sri Atmaja Rosyidi,; Mohd. Raihan. Taha,; Khairul Anuar Mohd Nayan, (2010)
Bearing capacity of the subgrade layers has significant influence on the performance of the overall pavement structure. In this study, the Spectral Analysis of Surface Wave (SASW) method was used for assessing the stiffness of pavement subgrade layer. The SASW method employed was based on the Rayleigh-wave propagation. Using the phase difference data of Rayleigh waves, the experimental dispersion curve of phase velocity was obtained. Consequently, inversion process was conducted to obtain the shear wave velocity and the dynamic modulus of the pavement structure. The results showed that some empirical models of the shear wave velocity and the dyamic elastic modulus versus soil bearing capacity of the California bearing ratio (CBR) and dynamic cone penetrometer (DCP) were derived. Good agreement was also found between these empirical models compared to that of previous studies